Plant invasion down under : exploring the below-ground impact of invasive plant species and their biological control on soil properties and invertebrate communities in the Central Plateau of New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology, Massey University, Palmerston North, New Zealand - Pearson, Benjamin Michael (Massey University, 2023)
With the increase in global trade and environmental disturbances, plant invasion continues to be one of the greatest threats to native ecosystems. The Central Plateau of New Zealand is of particular interest as it is home to several invasive plant species and biological control agents of these plants. Previous research has focused on the plant community responses of above-ground arthropods to plant invasions, but to my knowledge, no research has investigated soil properties and soil fauna communities at an individual plant level and compared these beneath native and invasive plants. Globally, information on post-release impacts of biological control agents on the below-ground communities and ecological processes is lacking, although we know that organisms such as foliar herbivores can impact the soil ecosystem indirectly, with consequences for control and subsequent recovery. This research aims to fill in this gap by investigating: 1) the soil properties and soil fauna communities associated with two native plant species (Leptospermum scoparium – mānuka, and Chionochloa rubra – red tussock) and two invasive species (Calluna vulgaris – heather and Cytisus scoparius – broom), and 2) how soil properties and soil fauna communities change under heather (C. vulgaris) plants at three stages of biocontrol agent (heather beetle) attack (prior, during and following the attack). In chapter 2, I sampled the soil physicochemical properties and macrofauna communities of two native and two invasive plant species. Rather than finding a difference between native and invasive plants as expected, I found a high degree of similarity between manuka and broom, and between red tussock and heather. This result highlighted the need to understand both the invasive and displaced vegetation when identifying impacts of invasion. In chapter 3, I sampled the soil ecosystem under heather plants before, during, and after feeding by the heather beetle. As expected, I found that the soil properties under heather differed before and during heather beetle attack. Unexpectedly, I found no difference in soil properties under heather before and after control by heather beetle. I also found that Collembola (springtails) and Oligochaeta (earthworms) were more abundant after heather beetle attack. Interestingly, Thysanoptera (thrips) abundances were highest prior to heather beetle attack, which could potentially have important consequences for biocontrol efficacy. These results provide some novel insights into the soil ecosystem responses to plant invasion, and the potential soil impacts post-biocontrol release, while highlighting the need for future research into a variety of plant species and control agents.
Keywords: 410202 Biosecurity science and invasive species ecology